Poverty Prevention through Right-using Technology Application - Prastyowati, Sri (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research is meant to know the perticipation of soya cake manufacturers in using used-water (IPAL) on poverty prevention in Grumbulmuntuk community, in Sukaraja Village, Banyumas District, Center Java Province. The research method is qualitative-descriptive to describe poverty condition soyabean cake manufacturer and their participation in using IPAL, and its poverty prevention alternative that can be done by related ministeries. Data are gathered through: interview with officials of local (social agency, environmental board, district social welfare workers and soyabean cake manufacturer); observation and library analysis. Data analysis done through qualitative-descriptive technique. The result can be concluded that the poverty prevention through right-using technology in soyabean cake manufaturers enviroment has not been optimally succesful yet because of its lack of participation based on their low income and education, no social and economic preparation, no intersectoral joint ventures, and continued guidance. It recommended that a guidance from the Ministery of Social Affairs and Research and Technology, through the placement of district social workers in rightusing technology (IPAL) should be done.